Carotid Doppler sonography: additional tool to assess hemodynamic improvement after transcatheter aortic valve implantation. Issue 3 (March 2018) - Cammalleri, Valeria; Romeo, Francesco; Marchei, Massimo; Anceschi, Andrea; Massaro, Gianluca; Muscoli, Saverio; De Persis, Francesca; Macrini, Massimiliano; Ussia, Gian P.
Abstract : Purpose: The aim of our study was to assess the arterial cerebral blood flow variations in patients with aortic valve stenosis, immediately after the transcatheter aortic valve implantation (TAVI). Methods: The study population includes 62 consecutive patients who underwent TAVI for aortic valve stenosis (95%) and sugical bioprosthesis degeneration (5%). Carotid Doppler examination was performed recording blood flow, systolic peak velocity, time average mean velocity and mean acceleration time at baseline, after balloon aortic valvuloplasty, and within 10 min after the device release. Results: A significant improvement of blood flow was recorded at the end of the procedure (from 315.05 ± 141.72 to 538.67 ± 277.46 ml/min; P < 0.00001). The systolic peak velocity and the time average mean velocity increased from 52.27 ± 14.29 to 78.89 ± 20.48 cm/s ( P < 0.00001) and from 12.24 ± 4.74 to 21.21 ± 9 cm/s ( P < 0.00001), respectively. Consensually, the mean acceleration time decreased from 0.22 ± 0.02 to 0.03 ± 0.02 s ( P < 0.00001) after the procedure. Conclusion: Monitoring of Doppler measurements may be a useful and noninvasive method to assess acutely the improvement of hemodynamic flow after TAVI, specifically for the cerebral district.